(untitled) (Latakia University Journal -Biological Sciences Series, 2018)
The aim of resarch was to study the effect of spraying with different concentrations of algebraic acid (0, 50, 100 ppm) and benzyl aminoporine (0, 25, 75 ppm) and both of them together in vegetative growth and flowering of the plant. The results showed the positive effect of the growth regulators on the development of the vegetative variety (length of plant, number of leaves, area of ​​paper surface and percentage of dry matter), as well as the formation and evolution of flowering date (early flowering, syphilis length, number of flowers on the inflorescence and floral diameter) use the highest concentration of both growth regulators (100, 75 ppm). The high concentrations of growth regulators also contributed to an increase in the life span of post-harvest flowers and significantly compared to the control . The previous positive effects were reflected significantly in economic efficiency, with transactions with growth regulators achieving higher economic profitability than the Control. هدف هذا البحث إلى دراسة تأثير الرش بتراكيز مختلفة من حمض الجبرلين (0، 50، 100 ppm)، وبتراكيز مختلفة من البنزيل أمينوبورين (0، 25، 75 ppm) بالإضافة إلى مزيج منهما في النمو الخضري والإزهار لنبات المنثور. أظهرت النتائج التأثير الإيجابي لمنظمي النمو في تطور المجموع الخضري (طول النبات وعدد الأوراق ومساحة المسطح الورقي و نسبة المادة الجافة)، بالإضافة إلى تشكل الشماريخ الزهرية وتطورها (التبكير في الإزهارو طول الشمراخ الزهري وعدد الأزهار على الشمراخ و قطر الأزهار) لاسيما عند استخدام التركيز الأعلى من كلا منظمي النمو (100، 75 ppm). كما ساهمت التراكيز المرتفعة من منظمي النمو في زيادة فترة حياة الأزهار ما بعد القطاف و بشكل معنوي مقارنة بمعاملة الشاهد. انعكست التأثيرات الإيجابية السابقة بشكل ملحوظ على الكفاءة الاقتصادية، حيث حققت المعاملات بمنظمي النمو ربحاً اقتصادياً أعلى من معاملة الشاهد.